Compulsive buying disorder: a review and update - Aboujaoude, Elias (Current pharmaceutical design, 2014)
Compulsive buying disorder (CBD) refers to the chronic purchasing of unneeded or unwanted items, causing significant negative consequences. There are no established criteria for CBD, and operational definitions have relied on similarities with OCD, substance use disorders, and impulse control disorders. Compulsive buying disorder is common, affecting 5.8% of the general population, according to one study. Typically, CBD has early onset, frequent comorbidities, and a chronic course. The etiology of CBD is unknown, with biological, psychological and sociocultural factors proposed as likely contributors. Treatment data are limited and suggest addressing comorbid conditions and considering cognitive behavioral therapy, financial and family counseling, selective serotonin reuptake inhibitors, and naltrexone, among other possible interventions, to target CBD. Beyond treatment, educational, legislative and family-based public policy initiatives can likely help individuals with CBD and other excessive spenders.